PENGARUH DISTINCTIVE CAPABILITIES PADA OBJEK WISATA ALAM TAMAN BUNGA NUSANTARA TERHADAP KEPUTUSAN BERKUNJUNG (Survei pada Wisatawan Taman Bunga Nusantara) - Nurwantika, Tia Aliana; Fakhrudin, Suwatno (Universitas Pendidikan Indonesia, 2012)
The great potential of Indonesian tourism with its diversity of objects and attractions, supported by facilities and infrastructures as well as the potential of qualified human resources, made tourism as one of a major core businesses in Indonesia, especially in West Java . The developing tourism industry in Indonesia has spur a competition among the enterpreneur which involved in tourism business. It also has a great impact to Taman Bunga Nusantara, which is one of tourism objects in Cianjur and located strategically between the area of Jakarta-Bandung. The development of Taman Bunga Nusantara is quite good, but it deals with decreased numbers of tourists visit in the year 2006-2010. This is due to several factors, one of these factor is the competition among tourism businesses subject in Puncak and the opened access of Cipularang toll, therefore it impacts to several number of tourism objects in Puncak-Cianjur especially Taman Bunga Nusantara. Therefore, Taman Bunga Nusantara tries to attract visitors by offering a unique tour to emphasize the concept of nature. The independent variable (X) is distinctive capabilities which consists of two dimensions which are Reputation and Innovation. The dependent variable (Y), namely the decision to visit. The type of the study is descriptive verifikatif, and the method used was survey which use sistematic sampling technique, so it obtains 100 respondents of samples. Techniques of data analysis and hypothesis test used was analyisis path (path analysis). The results showed that the distinctive capabilities provide a significant influence on the decision to visit. The biggest influence of distinctive capabilities of the Keputusan Berkunjung obtained through reputation and the smallest influence obtained through innovation. As for suggestions for the company in improving the decision to visit the Taman Bunga Nusantara is through the development of distinctive capabilities and a greater planning and innovative.